Assessment of Nurses’ Knowledge and Self-Reported Beliefs Regarding Inhaler Therapy in Bronchial Asthma and Chronic Obstructive Pulmonary Disease: Self-Reported Beliefs Regarding Inhaler Therapy in Bronchial Asthma and COPD - Adnan, Muhammad; Abbas, Taswar; Parvez, Mahnoor; Kareem, Mubashira; Tariq, Iqra; Shoukat, Maliha; Iqbal, Zafar (NURSEARCHER (Journal of Nursing & Midwifery Sciences), 2026)
Bronchial asthma and chronic obstructive pulmonary disease (COPD) are important diseases to treat with inhaled medications, but their effectiveness relies on proper device use. Objective: To evaluate nurses’ knowledge and self-reported beliefs regarding inhalation therapy devices, metered dose inhalers (MDIs), spacers, and dry powder inhalers (DPIs) in two hospitals in Multan, Pakistan. Methods: The descriptive cross-sectional study was done with Consecutive sampling for six months. A total of 115 nurses were enrolled in the sample. Nurses were given a self-developed 20-item yes/no questionnaire with a Cronbach’s alpha of 0.78 in the two hospitals: Medicare Hospital and Nishtar Hospital. Patients were excluded if they were nursing students or non-clinical staff, and registered nurses were included who had worked with patients for ≥1 year. Results: There was a significant lack of knowledge. As far as general knowledge was concerned, 58.3% of them thought inhalers are addictive, 43.5% believed inhalers to be a “last resort”, and more than 67% were misinformed about inhalers leading to weight gain and stunted growth. The critical technique errors were common: 61.7% thought patients should breathe in before pressing the MDI canister, and 16.5% did not know that MDIs should be shaken before use. Only 26.1% had good knowledge. The best predictor of adequate knowledge was prior training (p=0.002). Conclusions: The nurses were found to have poor knowledge of inhaler therapy. There is an urgent need for structured, device-specific training, along with supervised competency assessment, to address patient education and improve treatment outcomes.